Simultaneous Spectrophotometric Estimation of 11Î²,17Î±-dihydroxy -4-pregnene-3,20-dione- 21-succinate and its 1(2)-Dehydrogenated Product During Bioconversion by Comamonas acidovorans MTCC 3364 - Neelam Lad1 and S. P. Pawar2, Kirti Pawar1*, (Recent Research in Science and Technology, 2010)
A spectrophotometric method for simultaneously estimating 11Î²,17Î±-dihydroxy-4-pregnene-3,20-dione 21-succinate and its 1(2)-dehydrogenated product has been developed using sulphuric acid chromogens. The method was used to follow the progress of bioconversion during C-1(2)-dehydrogenation by Comamonas acidovorans MTCC 3364. Keywords: Steroid 1(2)-dehydrogenation; Simultaneous estimation; Steroid bioconversion; Hydrocortisone; Prednisolone estimation